Economic problems and planning in Pakistan : for B.A., M.A. & C.S.S. examinees - Mannan, M. A. ([Lahore : Ferozsons, 1968)
This book is a comprehensive review of economic problems and planning in Pakistan.
Include bibliographical references
oo 30/07/2018
Loans
Keywords: Economic problems; Economic planning; Pakistan; Pakistan